Protein folding and surface interaction phase diagrams in vitro and in cells. Issue 9 (27th March 2021) - Gruebele, Martin
Abstract : Protein stability is subject to environmental perturbations such as pressure and crowding, as well as sticking to other macromolecules and quinary structure. Thus, the environment inside and outside the cell plays a key role in how proteins fold, interact, and function on the scale from a few molecules to macroscopic ensembles. This review discusses three aspects of protein phase diagrams: first, the relevance of phase diagrams to protein folding and function in vitro and in cells; next, how the evolution of protein surfaces impacts on interaction phase diagrams; and finally, how phase separation plays a role on much larger length‐scales than individual proteins or oligomers, when liquid phase‐separated regions form to assist protein function and cell homeostasis. Abstract :